THE EFFECT OF STOCKING DENSITY OF FRESHWATER LOBSTER (Cherax quadricarinatus) THE GROWTH OF GOURAMY (Osphronemus gouramy) IN POLYCULTURE SYSTEM - Safitri, Anisa Dian; Mujtahidah, Tholibah; Sari, Novita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Polyculture is cultivation in one container that produces more than one species of fish simultaneously. The purpose of this study is to determine the effect on the growth of gouramy in polyculture system. This study uses an experimental method of Completely Randomized Design (CRD) 4 treatments and 4 repetitions that is P1 (15 species gouramy), P2 (10 species of limnetic lobster ad is species of gouramy), P3 (15 species of limnetic lobster and 15 species of gouramy), and P4 (20 species of limnetic and 15 species of gouramy). The data analysis used is analysis of variance (ANOVA) and Duncan’s Multiple Range Test (DMRT) for futher test, while the quality of water is analysed descriptively. The observation result show that different stocking density treatment affects absolute length growth of gouramy (O.gouramy). This is because the stocking density of limnetic lobster (C. quadricarinatus) is different for each treatment on gouramy (O. gouramy). The highest average result of measure ment of absolute weight growth is 1,45 ± 0,017 g. This is because the stocking density of limnetic lobster (C. quadricarinatus) at P2 is low. Low stocking density provides suitable space for gouramy to move and live. The maintenance of the polyculture system is better done with 10 species of limnetic lobster and 15 species gouramy because it makes the best absolute length and weight growth.